Expansion Strategy of PT Telekomunikasi Indonesia Tbk Through ITS Subsidiary Company (case study: Acquisition of Tiphone by Pins) - Khairunisa, Lintang; Koesrindartoto, Deddy P (The Indonesian Journal of Business Administration, 2015)
Abstract.The transformation of ICT industry was performed in order to avoid the decreasing company’s profit due to dissatisfaction of costumer. For instance, PT Telekomunikasi Indonesia (Telkom) has changed the business model from infocom (information and communication) became TIMES (Telecommunication, Information, Media, Edutainment and Services). One of the strategies of diversification is performed acquisition with company who has positive synergy and in October 2014, Telkom officially acquire Tiphone through its subsidiary which is PINS for 25%. The analysis shown that the Telecommunication Industry in Indonesia have been entered the phase of mature business. To keep sustain in this condition, Telkom has a plan to create an ICT ecosystem in its group. Therefore, Telkom want to acquire Tiphone in order to develop its business in device sector. Telkom estimate that Tiphone is a compromise company to be acquired since Tiphone has increasing gross profit margin, EBIT margin and Net Income margin every year and has CAGR as much as 19%, besides Tiphone also produce the low price cellular phone.Valuation of Discounted Cash Flow shows that the acquisition price of Tiphone is 1.52 trillion but PT PINS which is Telkom’s subsidiary company, acquire Tiphone only for 1.39 trillion which is undervalued. Moreover, Telkom and Tiphone have a positive synergy, reflected by the performance between 2 companies in cooperating of the migration process of flexi users into Telkomsel users. In this Final project, proposed that Tiphone should focus in produce Smartphone than feature phone. Thus, Tiphone can provide the Smartphone for flexi user in migration process. .Keywords: Expansion, Acquisition, Device, Discounted Cash Flow Analysis